PENERAPAN INTERVENSI MENGGAMBAR PADA PASIEN SKIZOFRENIA DENGAN HALUSINASI PENGLIHATAN DAN PENDENGARAN : CASE REPORT - Amelia, Gina Sri; Rafiyah, Imas; Widianti, Efri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Schizophrenia symptoms may vary among individuals, but one of the most common symptoms is hallucinations. Hallucinations can be treated using drawing as a non-pharmacological intervention. The purpose of this study was to examine the reduction in auditory and visual hallucination symptoms in schizophrenia patients after receiving drawing intervention. The research utilized a clinical case report method following five stages of nursing care, from assessment to evaluation. The study focused on a single schizophrenia unspecified patient experiencing auditory and visual hallucinations. The patient underwent drawing intervention sessions, consisting of drawing activities, conducted three times over three consecutive days, with each session lasting 30 minutes to 1 hour. The evaluation revealed that most hallucination symptoms disappeared, leaving only one symptom with reduced intensity. The study concluded that implementing drawing intervention can reduces auditory and visual hallucination symptoms in schizophrenia patients.